2016
DOI: 10.1186/s10194-016-0660-7
|View full text |Cite
|
Sign up to set email alerts
|

Release of PACAP-38 in episodic cluster headache patients – an exploratory study

Abstract: BackgroundActivation of the trigeminal-autonomic reflex, involving the trigeminal ganglion, the superior salivatory nucleus and the sphenopalatine ganglion (SPG) is crucial in the pathophysiology of cluster headache (CH). Since pituitary adenylate cyclase-activating polypeptide-38 (PACAP-38) is present both in the SPG and the trigeminal ganglion (TG) and its role in migraine has been described, our aim was to determine the plasma PACAP-38 levels in different phases of episodic CH (ECH).Peripheral cubital fossa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 36 publications
4
73
2
2
Order By: Relevance
“…A recent study in cerebrospinal fluid, in which significantly reduced hypocretin peptide levels were found in cluster headache patients39, further indicates that analysis of other tissues than blood is required to identify all genes and pathways involved in cluster headache. Then again, the worth of blood is supported by the finding that several biomarkers, including PACAP-3840 and methionine-enkephalin41, show altered levels during the course of a cluster headache attack in blood plasma.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in cerebrospinal fluid, in which significantly reduced hypocretin peptide levels were found in cluster headache patients39, further indicates that analysis of other tissues than blood is required to identify all genes and pathways involved in cluster headache. Then again, the worth of blood is supported by the finding that several biomarkers, including PACAP-3840 and methionine-enkephalin41, show altered levels during the course of a cluster headache attack in blood plasma.…”
Section: Discussionmentioning
confidence: 97%
“…PACAP might play a role in migraine having various neurobiological functions such as inhibitory effect on neurogenic inflammation [38]. PACAP has shown to be involved in trigeminovascular activation as PACAP-38 infusion caused headache in healthy volunteers [39] and PACAP-38-like immunoreactivity has proved to be altered in ictal compared to interictal phase of migraine and in cluster headache [40, 41]. It is suggested that the effect of PACAP is biphasic: lower concentration increasing, higher concentration inhibiting the NMDA receptor activation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PACAP administration in healthy subjects induces migraine-like headache [31]. PACAP, through PACAP receptor, induces activation of neurons in the superior salivatory nucleus, sphenopalatine and Gasser ganglion [32], that is thought to be a crucial event in CH pathophysiology, and higher PACAP plasma levels were detected during ictal phase than during inter-bout periods in CH patients [33]. …”
Section: Discussionmentioning
confidence: 99%